Influence of High Temperatures and Heat Wave on Thermal Biology, Locomotor Performance, and Antioxidant System of High-Altitude Frog Nanorana pleskei Endemic to Qinghai-Tibet Plateau - He, Jie; Tang, Xiaolong; Pu, Peng; Zhang, Tao; Niu, Zhiyi; Meng, Fei; Xi, Lu; Ma, Ming; Wu, Juan; Ma, Miaojun; Chen, Qiang (Frontiers in Ecology and Evolution, 2021)
Investigating how highland amphibians respond to changes in ambient temperature may be of great significance for their fate prediction and effective conservation in the background of global warming. Here, using field individuals as the control group, we investigated the influence of high temperatures (20.5 and 25.5°C) and heat wave (15–26.6°C) on the thermal preference, critical thermal limits, locomotor performance, oxidative stress, and antioxidant enzyme activities in high-altitude frog Nanorana pleskei (3,490 m) endemic to the Qinghai-Tibet Plateau (QTP). After 2 weeks of acclimation to high temperatures and heat wave, the thermal preference (Tpref), critical thermal maximum (CTmax), and range of tolerable temperature significantly increased, while the critical thermal minimum (CTmin) was significantly decreased. The total time of jump to exhaustion significantly decreased, and burst swimming speed significantly increased in frogs acclimated in the high temperature and heat wave groups compared with the field group. In the high temperature group, the level of H2O2 and lipid peroxide (malondialdehyde, MDA), as well as the activities of glutathione peroxidase (GPX), glutathione reductase (GR), catalase (CAT), superoxide dismutase (SOD), and total antioxidant capacity (T-AOC) significantly increased in the liver or muscle. However, in the heat wave group, the MDA content significantly decreased in the liver, and antioxidants activities decreased in the liver and muscle except for CAT activities that were significantly increased in the liver. These results indicated that N. pleskei could respond to the oxidative stress caused by high temperatures by enhancing the activity of antioxidant enzymes. The heat wave did not appear to cause oxidative damage in N. pleskei, which may be attributed to the fact that they have successfully adapted to the dramatic temperature fluctuations on the QTP.